Studi Awal Pengembangan dan Validasi Instrumen ketahanan Akademik (Academic Buoyancy) pada Mahasiswa Tingkat Akhir - Retno Fajarwati; Wardani Utami Dewi; Binti Isrofin; Muhammad Naim Almarham (Universitas Nusantara PGRI Kediri, 2026)
Undertaking an undergraduate thesis is a demanding academic phase frequently accompanied by stress and anxiety, underscoring the importance of academic buoyancy, the capacity to deal with everyday academic setbacks. This preliminary study aimed to develop an academic buoyancy instrument for final-year students based on the 5C framework (confidence, coordination, control, composure, and commitment) and to conduct an initial psychometric evaluation through expert judgment, item-total correlation analysis, and internal consistency estimation. Following Azwar's scale development stages, an initial pool of 25 Likert-type items was reviewed by two experts; Content validity was rated highly feasible (subject expert 96%, language expert 86%; mean 91%). The instrument was administered to 104 students writing or about to write their theses. Item-total correlations ranged from 0.103 to 0.495; 24 items met the criteria (p < 0.05) and one item (i3) was removed. The final 24 item set yielded a Cronbach's alpha of 0.742, adequate for an early stage instrument and a basis for further validation rather than high-stakes individual decisions.